Description of Borax in Wet Yellow Noodles at Pontianak Market - Iswono; Dewi Rahmi Salsabilla Cahyanto; Salbiah Kastari; Bambang Prayitno (Jurnal teknologi Kesehatan Borneo, 2021)
Wet Yellow Noodles is a popular cuisine because its convenient, and quick to prepare. Because the water content can reach 52%, the shelf life is limited. Borax is a preservative that can be used to extend the life of Wet Yellow Noodles, despite the fact that its use in food is prohibited. The aim of the study was to assess whether or not there was Borax in the Wet Yellow Noodles sold at the Pontianak City. The research was carried out in February-July 2021. Sample of this research is Wet Yellow Noodles which was purchased from the Pontianak City Market, and its a descriptive study conducted by observation. Total of 19 samples was observed, 6 samples of borax were negative, 9 samples of borax were positive with levels < 50 ppm, 4 samples of borax were positive with levels > 50 – 500 ppm. Total of 19 samples whose physical characteristics observed showed that 6 samples tended not to contain Borax, while 13 samples inclined to contain Borax. The expertise level of Wet Yellow Noodle traders at the Pontianak City Market, with good category of 10,5%, sufficient category of 36,9%, and less category of 52,6%. The attitude of the Mie Kuning Wet traders at the Pontianak City Market is described as having an excellent category of 42,1% and an adequate category of 57,9%. The conclusion from this study that the majority of the Wet Yellow Noodles samples tested were unhealthy to eat because they contained borax. Traders' understanding of the presence of borax in food is still quite limited.